2013
DOI: 10.7314/apjcp.2013.14.4.2509
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Supraclavicular Lymph Node Recurrence in N1 Breast Cancer Patients

Abstract: Background: The purpose of this study was to identify predictive factors for supraclavicular lymph node recurrence (SCLR) in N1 breast cancer patients and define a high-risk subgroup who might benefit from supraclavicular nodal radiotherapy (RT). Materials and Methods: From January 1995 to December 2009, 113 breast cancer patients with 1 to 3 positive axillary lymph nodes were enrolled in this study. All patients underwent breast-conserving surgery (BCS) or modified radical mastectomy (MRM). RT was given to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…This suggests that patients receiving mastectomy due to T1-2N1M0 breast cancer should have postoperative RT targeted at the supra-/infraclavicular lymphatic drainage area. A similar conclusion was reached in a study of 113 breast cancer patients with 1 to 3 positive axillary lymph nodes who underwent BCS or modified radical mastectomy (MRM) (Kong and Hong, 2013). Kong et al (2013) also concluded that supraclavicular nodal RT was necessary in N1 breast cancer patients.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…This suggests that patients receiving mastectomy due to T1-2N1M0 breast cancer should have postoperative RT targeted at the supra-/infraclavicular lymphatic drainage area. A similar conclusion was reached in a study of 113 breast cancer patients with 1 to 3 positive axillary lymph nodes who underwent BCS or modified radical mastectomy (MRM) (Kong and Hong, 2013). Kong et al (2013) also concluded that supraclavicular nodal RT was necessary in N1 breast cancer patients.…”
Section: Discussionsupporting
confidence: 52%
“…A similar conclusion was reached in a study of 113 breast cancer patients with 1 to 3 positive axillary lymph nodes who underwent BCS or modified radical mastectomy (MRM) (Kong and Hong, 2013). Kong et al (2013) also concluded that supraclavicular nodal RT was necessary in N1 breast cancer patients. However, they limited their therapeutic approach to only a high-risk subgroup of patients featuring histologic grade 3 and ECE.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations